The Effect of Health Education on Knowledge and Attitudes about Anemia in Adolescent - Elvi Destariyani (International Journal of Health Sciences, 2025)
Anemia is a disease where hemoglobin levels in red blood cells are lower than normal due to a lack of important food elements. The prevalence of adolescent anemia in Bengkulu increased by 9.3% from 2013 – 2018. The aim of the research was to determine the effect of health education on the knowledge and attitudes of adolescent girls about anemia in SMP N Bengkulu City. This quantitative research uses the Quasi Experimental Pretest-Posttest method with a control group. The total sample was 52 young women, each group had a sample of 26 young women. Analysis of knowledge data used the Wilcoxon Signed Rank Test and Mann Whitney Test, for attitudes used Paired Samples T Test and Independent Samples T Test. Statistical test results of the mean knowledge of the crossword game group (92.42), monopoly game group (80.69) mean difference (11.73), statistical test results of the mean attitude of the crossword game group (56.08), monopoly game group (50.58), the mean difference (5.5), this shows that the increase in the knowledge & attitude scores of the intervention group was higher than the control group.